2006
DOI: 10.1161/01.str.0000244763.19013.dc
|View full text |Cite
|
Sign up to set email alerts
|

Combined Measurement of Carotid Stiffness and Intima-Media Thickness Improves Prediction of Complex Aortic Plaques in Patients With Ischemic Stroke

Abstract: Background and Purpose-We hypothesized that for the prediction or exclusion of aortic thrombi or plaques Ն4 mm, the combination of intima-media thickness (IMT) and distensibility (DC) of the common carotid arteries would be superior to the measurement of IMT alone. Methods-We prospectively included 208 stroke patients (mean age, 60 years) undergoing transesophageal echocardiography for screening of aortic plaques. IMT and DC were determined by ultrasound, and DC was quantified by measuring blood pressure and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 19 publications
1
45
0
2
Order By: Relevance
“…Our findings are consistent with recent studies suggesting the use of CIMT testing for the exclusion of significant aortic atheroma. 8,9,17 In a prospective study, Harloff et al reported that use of CIMT testing achieved a negative predictive value of 92% for the detection of complex aortic atheroma. 9 Complex aortic plaques are particularly important to exclude because they are associated with a increased risk of recurrent stroke and may warrant therapy with statins or warfarin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with recent studies suggesting the use of CIMT testing for the exclusion of significant aortic atheroma. 8,9,17 In a prospective study, Harloff et al reported that use of CIMT testing achieved a negative predictive value of 92% for the detection of complex aortic atheroma. 9 Complex aortic plaques are particularly important to exclude because they are associated with a increased risk of recurrent stroke and may warrant therapy with statins or warfarin.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,17 In a prospective study, Harloff et al reported that use of CIMT testing achieved a negative predictive value of 92% for the detection of complex aortic atheroma. 9 Complex aortic plaques are particularly important to exclude because they are associated with a increased risk of recurrent stroke and may warrant therapy with statins or warfarin. 18 -21 Additionally, we have previously reported that complex aortic plaques are the only individual CSE found on TEE after ischemic stroke to be associated with an increased mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of PAD may indicate the terminal stage of systemic atherosclerosis. [27][28][29] On multivariate logistic regression analysis, the independent factors associated with ACL were age, smoking and the presence of PAD. Age and smoking were earlier reported to be risk factors for ACL.…”
Section: Discussionmentioning
confidence: 99%
“…A minimum of 4 measurements of the common carotid far wall were taken 10 mm proximal to the bifurcation to derive mean carotid intima-media thickness (IMT) [13]. We considered carotid IMT to be normal when IMT was ≤0.9 mm and increased when IMT was >0.9 mm [14]. Carotid artery plaque was assessed according to standard scanning and reading protocols [15].…”
Section: Methodsmentioning
confidence: 99%